Accounting for Unintended Consequences in IS Research: A Call to Action - Benbya, Hind; Strich, Franz; Trieu, Van-Hau (Australasian Journal of Information Systems)
Unintended consequences in Information Systems (IS) research are typically examined only after they have surfaced in practice, often treated as isolated instances rather than being systematically identified and understood. This reactive stance constrains our ability to anticipate risks, recognize emerging opportunities, and build cumulative insights across studies. To assess the current state of IS research on unintended consequences, we conducted a scoping review of literature in the Association for Information Systems' Senior Scholars' Basket of Journals. Our review highlights significant gaps in how unintended consequences are defined, theorized, and systematically compared. To address these gaps, we propose three foundational considerations: (1) conceptual clarity, to refine definitions and delineate boundaries; (2) relational configurations, to analyze the interplay between actors, technologies, and contexts; and (3) temporal configurations, to capture the evolving nature of consequences over time. Building on these dimensions, we introduce a set of guiding questions designed to provide shared analytical vocabulary rather than a prescriptive framework. These questions enable researchers to more systematically identify, categorize, and compare unintended consequences across contexts, thereby fostering theoretical precision, facilitating cross-contextual learning, and supporting a more anticipatory and comprehensive understanding of the phenomenon.

Overview on Threshold Signature Schemes and their Applications - Anonymous, A.

Comparison of Time-Lock Puzzle Constructions and Their Security - Anonymous, A

Damage-incorporated four-step mean-field method for simulating CFRP machining: a novel algorithmic approach - Zhan, Yingjie; Caylak, Ismail; Ostwald, Richard; Barth, Enrico; Uhlmann, Eckart (Multiscale and Multidisciplinary Modeling, Experiments and Design)

Unraveling the head-fake effect: Dynamic measures of cognitive conflict in sport contexts - Güldenpenning, Iris; Schulze Freilinghaus, Lars; Böer, Nils Tobias; Weigelt, Matthias (57. Herbsttagung experimentelle Kognitionspsychologie (HexKop))

Mercedes. Gunst und Affekt in Cervantes’ La española inglesa - Schlieper, Hendrik (Artes)

Look Who's Talking: Multivoicedness in Students’ Descriptions of Their Disciplines - Schmöckel, Sabrina

The Culture Quest – Students Decode Their Disciplinary Culture(s) - Schmöckel, Sabrina

Does the Future Have a Lobby? Environmental Degradation and Perceived Environmental Responsibility towards Future Generations - Diekmann, Isabell; Faist, Thomas (Environmental Sociology)
The devastating consequences of environmental degradation are increasingly evident, necessitating both adaptation and mitigation strategies. This study investigates perceived individual responsibility, drawing upon Hans Jonas’ "The Imperative of Responsibility" as a theoretical framework. Our aim is to explore the relationship between five independent variables (perceived climate change threat, trust in technological progress, religiosity, responsibility for contemporaries impacted by natural disasters, and environmental concern) and the dependent variable of perceived environmental responsibility towards future generations. Findings reveal that approximately 77 percent of respondents in Germany are willing to sacrifice current standards of living to protect the environment for future generations. Notably, perceiving climate change as a threat, assuming responsibility for present-day impacts and environmental stewardship emerge as significant predictors of environmental responsibility towards future generations. Being religious also correlates with heightened environmental responsibility compared to non-religious individuals. Trust in technological progress only weakly correlates with intergenerational environmental responsibility, surprisingly suggesting a positive relationship. These findings provide valuable insights into determinants of perceived individual responsibility. In order to arrive at a more complete analysis, however, future research needs to complement this study of perceived individual-level responsibility with considerations on collective actors and structural factors.

İslam düşmanlığı, Müslüman düşmanlığı ve Müslüman karşıtı ırkçılık: Kavramsallaştırmaya yönelik farklılaştırıcı ve bütünleştirici yaklaşımlar - Diekmann, Isabell (Türkisch-Deutsche Perspektiven / Türk-Alman Bakis Açilari)
Bu makale, Müslümanlara ve Islam’a karsi önyargi ve ayrimcilikla ilgili farkli terim ve kavramlara odaklanmaktadir. Bu bölümdeki farklilastirma öncelikle bu düsmanligin farkli muhataplariyla ilgilidir. Buradaki soru, Islam dinine yönelik düsmanca tutumlarin, Müslümanlara yönelik düsmanca tutumlarla ne ölçüde ayni oldugudur. Ayni zamanda bu makale, bireysel tutum olarak Islam/Müslüman düsmanliginin ve yapisal bir özellik olarak Müslüman karsiti irkçiligin farkli düzeylerde konumlandigi konusunda farkindalik yaratir. Makale iki arastirma geleneginin (irkçilik ve önyargi arastirmalari) farkli paradigmalarini göstermekte, fakat ayni zamanda bireysel ve yapisal düzeyler yogun bir sekilde iç içe geçtigi için kavramlarin bütünlestirici bir sekilde anlasilmasini savunmaktadir. Çalisma, Islam/Müslüman düsmanligi ve Müslüman karsiti irkçilikla mücadeleye yönelik teorik, metodolojik ve özellikle pratik çikarimlarin genis bir tartismasiyla sonuçlanir.
Keywords: Islam düsmanligi; Müslüman düsmanligi; Müslüman karsiti irkçilik; Önyargi; Ayrimcilik; Din; Birey; Yapi

The Puzzle of Loneliness: A Sociostructural and Transnational Analysis of International Chinese Students’ Networks in Germany - Bilecen, Basak; Diekmann, Isabell; Faist, Thomas (International Migration)
The experience of loneliness is common among international students who study in a foreign country, away from their home. Loneliness refers to the difference between the actual and desired social relationships highlighting not only the quantity but also the quality of relationships. We argue for a perspective on loneliness that emphasizes its social context rather than relying mainly on individualistic or psychological interpretations prevalent thus far. In this article, we explore network predictors of loneliness among Chinese international students in Germany. Through our analysis of a unique data set, we show that when compared to the local students, international students tend to feel lonelier. Surprisingly, when we discover that when international students have the same network size, those with more emotionally supportive ties tend to experience more loneliness compared to those with fewer emotionally supportive ties. Not surprisingly, having a romantic partner is associated with lower levels of loneliness, especially when they also live in the country of education. Additionally, we find that international Chinese students who struggle to form cross‐national friendships report higher levels of loneliness. By delving into these findings, our research offers a sociological account of loneliness among international Chinese and local students in Germany.

Islamfeindlichkeit, Muslim*innenfeindlichkeit und antimuslimischer Rassismus: differenzierende und integrative Ansätze zur Konzeptionalisierung - Diekmann, Isabell (Türkisch-Deutsche Perspektiven / Türk-Alman Bakis Açilari)
Dieser Beitrag fokussiert unterschiedliche Begriffe und Konzepte im Zusammenhang mit Vorurteilen und Diskriminierung gegenüber Muslim* innen und dem Islam. Die Differenzierung in diesem Kapitel bezieht sich vor allem auf unterschiedliche Adressat*innen von Feindlichkeit. Dabei geht es um die Frage, inwiefern feindliche Einstellungen gegenüber der Religion des Islams identisch sind mit feindlichen Einstellungen gegenüber muslimischen Menschen. Gleichzeitig sensibilisiert dieser Beitrag für die unterschiedlichen Ebenen, auf denen Islam-/Muslim*innenfeindlichkeit als individuelle Einstellungen und antimuslimischer Rassismus als Strukturmerkmal verortet sind. Er zeigt die unterschiedlichen Paradigmen der beiden Forschungstraditionen (Rassismus- und Vorurteilsforschung) auf, argumentiert aber auch für ein integratives Verständnis der Konzepte, da die individuelle und strukturelle Ebene eng miteinander verwoben sind. Der Beitrag schließt mit einer breiten Diskussion um theoretische, methodologische und insbesondere handlungspraktische Implikationen im Umgang mit Islam-/Muslim*innenfeindlichkeit und antimuslimischem Rassismus.
Keywords: Islamfeindlichkeit; Muslim*innenfeindlichkeit; Antimuslimischer Rassismus; Vorurteile; Diskriminierung; Religion; Individuum; Struktur

Geschichte und Umwelt von Rechenzentren; Rezension zu: Dommann, Monika; Rickli, Hannes; Stadler, Max (Hrsg.): Data Centers. Edges of a Wired Nation, Zürich 2020; Gugerli, David; Wichum, Ricky: An den Grenzen der Berechenbarkeit. Supercomputing in Stuttgart, Zürich 2021 - Schmitt, Martin (HSozKult)
Keywords: Rechenzentren; Geschichte; Umweltgeschichte; Nachhaltigkeit; Supercomputing; Technikgeschichte

Optimization Techniques for Sustainable Energy System Design - Burmeister, Sascha Christian
Diese Dissertation untersucht Optimierungsverfahren für die nachhaltige Gestaltung von Energiesystemen mit Schwerpunkt auf dem Elektrizitätssektor im Kontext der Energiewende. Aufbauend auf Methoden des Operations Research werden Planungs- und Steuerungsprobleme in den Bereichen Stromverteilnetze und energiebewusste Produktionsplanung adressiert. Die Arbeit umfasst fünf Beiträge: (P1) entwickelt ein lineares Multi-Commodity-Flow-Modell für die kostenoptimale Erweiterung großskaliger Verteilnetze unter Berücksichtigung von Resilienzszenarien und analysiert den Zusammenhang zwischen Modellparametern und Rechenzeiten; (P2) und (P3) befassen sich mit der mehrzielorientierten flexible Job Shop Scheduling-Optimierung unter Echtzeit-Strompreisen, wobei (P3) zusätzlich CO2-Emissionen als Zielgröße integriert; (P4) erweitert dieses Szenario um simultane Energiebeschaffungsentscheidungen aus Netz, erneuerbaren Quellen und Speichersystemen unter Unsicherheit mittels Rolling-Horizon-Ansatz; (P5) vergleicht unterschiedliche Klassen von Many-Objective Evolutionary Algorithms (dominanz-, indikatoren- und dekompositionsbasiert) im Hinblick auf Konvergenz, Diversität und Vollständigkeit der Paretofront. Die entwickelten Modelle und Algorithmen – darunter memetische Varianten von NSGA-II, NSGA-III, θ-DEA und HypE – werden durch umfassende Rechenexperimente evaluiert. Die Ergebnisse liefern praxisrelevante Handlungsempfehlungen für Netzbetreiber, produzierende Unternehmen und politische Entscheidungsträger und leisten einen Beitrag zur effizienten, zuverlässigen und emissionsarmen Energieversorgung der Zukunft.

Wohlverhaltenspflichten nach § 63 Abs. 4, Abs. 5 WpHG (Product Governance) - Bartlitz, David (iff Infobrief)

AI-Based Management and Generation Of Non-Functional Requirements in Vehicle Development and Integration - Bazzal, Mahmoud; Lungu, Adriana; Kruse, Benjamin; Bernijazov, Ruslan; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: As modern technical systems grow in complexity, ensuring the quality of these systems during early development phases becomes more challenging. This is particularly evident in the development of modern passenger vehicles, where non-functional requirements (NFRs) play a critical role in ensuring that a vehicle operates according to specified standards and expectations, especially across different vehicle configurations and environmental conditions. The introduction of Artificial Intelligence (AI) in automotive engineering has transformed the approach to vehicle system design and development. This paper presents a pipeline for analyzing and generating NFRs for vehicle systems using generative AI-based methods. The pipeline categorizes NFRs, explores their interdependencies with vehicle configurations and environmental conditions, and addresses the completeness of NFRs in relation to specific vehicle use cases. The paper focuses on selecting appropriate NFR types for various use cases, taking into account diverse configurations and environmental factors. Examples of NFRs with varying parameters are provided for an electric vehicle under development at a leading car manufacturer, illustrating the benefit as well as the challenges of applying generative AI to automotive engineering.

Navigating viewpoints in MBSE: challenges, potential and pathways for stakeholder participation in industry - Förster, Felix; Koldewey, Christian; Bernijazov, Ruslan; Dumitrescu, Roman; Bursac, Nikola (Proceedings of the Design Society)
ABSTRACT: Model-based Systems Engineering (MBSE) supports managing complex engineering projects. A pivotal element of MBSE is the concept of views which provide tailored representations of a system model to address stakeholder concerns. Despite standards describing the use and generation of views, the adoption and practical implementation of MBSE views and viewpoints in industrial practice remain insufficiently explored. Interviews with German practitioners reveal a disconnect between theory and practice: views and viewpoints and the involvement in MBSE are often limited to technical experts, excluding non-technical stakeholders. High complexity, abstract representations, and tool-related barriers impede broader engagement. The findings suggest stakeholder-specific, accessible visualizations integrated into easy-to-use tools to improve understanding, collaboration, and decision-making.

Digital engineering transformation for sustainability: an approach to systematically integrate sustainability data in engineering processes - Wyrwich, Fabian; Könemann, Ulf; Tissen, Denis; Bohnenkamp, Tinus; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: Digital engineering transformation in industrial companies requires addressing diverse needs and their impact on every impacted engineering aspect. This paper analyses Changes initiated by transformation drivers and presents a systematic approach to integrate sustainability into engineering processes and artifacts. As a currently important topic the integration of sustainability data in engineering is used as an example of application. Based on identified use cases, sustainability parameters are derived and linked to engineering data objects to pinpoint their placement within the early product development. The results demonstrate how data-driven approaches enable effective sustainability integration and provide a foundation for future digital engineering transformations due to diverse divers.

Integrative and Integrated product and production system development: a taxonomy for managing dependencies and processes - Disselkamp, Jan-Philipp; Seidenberg, Tobias; Westphal, Svenja; Lick, Jonas; Ptock, Lukas; Wyrwich, Fabian; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The increasing complexity of modern product and production system development, driven by dynamic market demands, supply chain disruptions and economic pressures, poses significant challenges for companies. Existing methodologies often fall short due to their domain-specific focus, inconsistent terminology and lack of integration. To address these challenges, this paper presents a taxonomy for integrative product and production system development. The taxonomy systematically structures key elements, dependencies and processes to improve collaboration, decision-making and communication within organisations. Developed iteratively the taxonomy identifies ten core artefacts. It enables organisations to better plan improvements, synchronise development processes, and select appropriate methods and tools.

Resilience-By-Design: Standard-based definition of Resilience and identification of action fields for the systems design of mobility system - Bita, Isaac Mpidi; Hovemann, Aschot; Dumitrescu, Roman (Proceedings of the Design Society)
ABSTRACT: The increasing complexity and connectivity of the mobility system and modern automotive systems, particularly connected autonomous vehicles, demand a paradigm shift toward resilience-by-design to address disruptions in dynamic environments. Unlike established safety and cybersecurity engineering in automotive, resilience engineering has yet to be systematically integrated into development processes. This paper defines resilience using a standard-based definition method, emphasizing disruption tolerance, adaptability, and recoverability. We identify action fields to advance the topic and propose a resilience-by-design framework extending safety and cybersecurity perspectives. Resilience-by-design offers strategies and methods to design robust, adaptive systems, ensuring reliability and availability of automotive systems, functions, and components in operation.